Scopoletin as a cardioprotective agent against cisplatin-induced oxidative stress and inflammation - Esam Qnais; Omar Gammoh; Yousra Bsieso; Mohammad Alqudah; Mohammad Wedyan; Sara Altaber; Alaa A.A. Aljabali; Abdelrahim Alqudah; Taher Hatahet (Phytomedicine Plus)
Background: Cisplatin (CP) is a chemotherapeutic agent notorious for its cardiotoxic effects. Scopoletin, a natural coumarin, has shown potential due to its antioxidant, anti-inflammatory, and anti-apoptotic properties, which may counteract CP-induced cardiotoxicity. Purpose: The study aimed to explore the cardioprotective effects of scopoletin against CP-induced damage in mice, focusing on histopathological changes, cardiac biomarkers, oxidative stress, inflammation, apoptosis, and the modulation of key signaling pathways. Study Design: A controlled experimental design was employed to evaluate scopoletin's efficacy in alleviating CP-induced cardiotoxicity, with dosing variations to assess dose dependency. Methods: Male mice were allocated into five groups: a control group, a cisplatin-only group, two groups treated with low (50 mg/kg/day) and high doses (150 mg/kg/day) of scopoletin in conjunction with cisplatin, and a scopoletin-only group. The interventions were administered over a period of one week, with cardiac damage assessed through histopathological examinations, serum cardiac biomarker measurements, and analyses of oxidative stress, inflammatory cytokines, and apoptosis-related proteins. The efficacy of scopoletin in modulating the p62/Keap1/Nrf2 pathway was also examined. Results: Histopathological assessments showed less tissue damage in scopoletin-treated groups (p < 0.01). Cardiac biomarkers were significantly lower in l- and H-scopoletin groups compared to the CP-only group (p < 0.05, p < 0.01). Scopoletin effectively reduced ROS and MDA levels while enhancing antioxidant enzymes like SOD, CAT, and GSH (p < 0.01). With scopoletin treatment, inflammatory cytokines TNF-α and IL-6 were notably reduced (p < 0.01). Apoptosis analysis revealed lower levels of pro-apoptotic proteins and higher levels of Bcl-2 in scopoletin groups (p < 0.05, p < 0.01). Significantly, scopoletin restored the function of the p62/Keap1/Nrf2 signaling pathway (p < 0.01). Conclusion: The findings suggest scopoletin's potential as an adjunctive therapy in cancer treatment to mitigate CP's adverse effects, warranting further clinical investigation.